Rethinking monolithic pathways to success and talent identification: The case of the women's Japanese volleyball team and why height is not everything - Vargas, J.; Loureiro, M.; Nikolaidis, P. T.; Knechtle, B.; Laporta, L.; Marcelino, R.; Afonso, J. (Journal of Human Kinetics, 2018)
The aim of the present study was to analyse the Japanese National Women`s Volleyball Team and to identify items differentiating it from other teams. All fifteen matches between the six National Teams (i.e., Japan, Brazil, China, Belgium, Turkey and Russia) competing at the Women`s Volleyball World Grand Prix Finals of 2014 were analyzed, in a total of 56 sets and 7,176 situations of ball possession. Data suggested the existence of differences between Japan`s and the other five teams` gameplay, namely the likelihood of more gameplay with utilization of the float jump serve (20.42; ± 3.79%, very large magnitude) and attack tempo 2 (61.89; ± 29.67%, large magnitude), while exhibiting less gameplay with zero blockers opposing the attack (-42.06; ± 21.28%, large magnitude). Based on these findings, it was concluded that sports success could be achieved even when a core feature of mainstream performance models (e.g., height in volleyball) was lacking.